Epistemic foundations of game theory - Giacomo Bonanno (University of California, Department of Economics, 2012)
This is the first draft of a chapter for the forthcoming Handbook of Epistemic Logic, edited by Hans van Ditmarsch, Joe Halpern, Wiebe van der Hoek and Barteld Kooi (College Publications). Contents: 1. Introduction 2. Epistemic Models of Strategic-Form Games 3. Semantic Analysis of Common Belief of Rationality 4. Syntactic Characterization of Common Belief of Rationality 5. Common Belief versus Common Knowledge 6. Probabilistic Beliefs and von Neumann- Morgenstern Payoffs 7. Dynamic Games with Perfect Information 8. The Semantics of Belief Revision 9. Common Belief of Rationality in Perfect-Information Games 10. Literature Review
Keywords: 330